Climate change and Egypt’s agriculture - Perez, Nicostrato D.; Kassim, Yumna; Ringler, Claudia; Thomas, Timothy S.; ElDidi, Hagar (International Food Policy Research Institute, 2021)
With climate change, Egypt’s already arid climate will face even higher temperatures and lower rainfall over key agricultural areas, requiring further urgent adaptation investments. Data from three general circulation models of climate were used to better understand the likely effects of climate changes on Egypt’s agricultural sector. The findings show largely adverse biophysical effects of climate change by 2050. Compared to a no-climate change scenario, yields for food crops are projected to decline by over 10 percent by 2050 due to higher temperatures and water stress as well as increased salinity of irrigation water. The highest biophysical yield declines are estimated for maize, sugar crops, and fruits and vegetables. Moreover, due to the country’s dependence on food imports, Egypt is not only affected by climate change impacts at home, but also by impacts in other food producing countries. Climate change-induced increases in food prices will reduce Egypt’s food import demand, while also dampening demand for Egypt’s exports. The implications for Egypt are tighter food markets with both reduced domestic production and increased difficulties to import food making it more difficult to augment domestic food supplies. This situation suggests the need for investments in climate change adaptation in the agriculture sector. Global cooperation to mitigate greenhouse gas emissions is also warranted given the high cost to Egypt’s society from adverse climate change impacts worldwide.